Fostering Literacy Culture by Optimizing Reading Corner at Elementary School - Susanti, Yunik; Kurnia, Ita; Nurhajati, Diani (Soegijapranata Catholic University, 2025)
Literacy is not just the ability to read and write, it involves the ability to understand, engage, use, analyze and transform both written and spoken texts. Schools have an important role in building a literacy culture in schools. One of them is creating a literacy-friendly physical environment. Reading corner is an example of a physical environment that supports the development of a literacy culture at school. This study aimed to study the implementation of reading corner activities in order to foster literacy culture as applied in an elementary school and to identify the students’ reaction to the activities in reading corners. This case study was carried out at Kaliombo elementary school Kediri. The data from school principals, teachers and students were gathered through interview, questionnaire and documentation. The data was analyzed using qualitative data analysis and percentage computation. The results showed that the literacy culture built in the reading corner was carried out in several ways: (a) composing a certain schedule for each class to read certain books and do activities in the reading corner; (b) providing interesting and varied new books to boost the students’ interest in the reading corner; (c) creating literacy-related activities in reading corner. The study finds that students had positive reactions to the implementation of activities in the reading corner to foster literacy culture. This study also implied that the reading corner is worth developing in elementary school as it facilitates students with numerous activities that encourage the formation of a literacy culture.